The Impact of Foreign Trade, Energy Consumption and Income on Co2 Emissions - AKIN, Cemil Serhat (International Journal of Energy Economics and Policy, 2014)
The aim of this study is to investigate the impact of energy consumption economic growth and especially trade openness on CO2 emissions. In this frame, determiners of the CO2 emissions are questioned by panel data cointegration analysis. In the scope of this study, 85 countries’ data are contributed to the analysis for the period of 1990-2011. According to the results positive relationship is found between CO2 emissions and energy consumption, per capita income and trade openness. On the other hand, trade openness can reduce CO2 emissions in the long run. Findings indicate that in the short run unidirectional causality from CO2 emissions to trade openness (TRD). Also there is unidirectional causality from per capita income (GDP) to CO2 emissions and energy consumption (EN). Short run dynamics suggest bidirectional causality from GDP to TRD and TRD2. According to the coefficient on the lagged ECT, implying that there are two long-run panel causality links that run from LGDP, LTRD and LEN, to LCO2 and from LGDP, LTRD and LCO2 emissions to LEN. Keywords: CO2 emissions; Trade Openness; Panel Cointegration Analysis; Panel causality analysis. JEL Classifications: C33; O13; Q43